An optimal design of the widths of heat affect zone, fusion zone, and near interface zone in a dissimilar metal welded joint. Issue 5 (26th November 2019) - Guo, Guoliang; Yang, Jie; Wang, Lei; Liu, Guiqiu; Zhang, Baozhong; Zhang, Sihan
Abstract: The optimal design of the dissimilar metal welded joint is a valuable research issue, whether optimize the material, processing technology, dimension, or anything else. The fracture behavior of the dissimilar metal welded joint have been found affected by the widths of heat affect zone, fusion zone, and near interface zone. In this study, the optimal design of the widths of heat affect zone, fusion zone, and near interface zone in the dissimilar metal welded joint was further studied systematically. Firstly, a dissimilar metal welded joint, which used in the nuclear power plants with either heat affect zone crack or fusion zone crack, was selected, and a width mismatch coefficient M W was defined. In addition, the crack propagation paths and J ‐resistance curves of the dissimilar metal welded joints under different M W induced by the widths of heat affect zone, fusion zone, and near interface zone were calculated. Based on the obtained results, the widths of heat affect zone, fusion zone, and near interface zone were optimized. This study will provide support for the design of the dissimilar metal welded joint and is significant to the structure integrity assessment of the nuclear power plants.